2018
DOI: 10.24843/jh.2018.v22.i03.p23
|View full text |Cite
|
Sign up to set email alerts
|

Morphosyntactic Study on English Derivational Suffixes Forming Adjectives with Reference to the Twilight

Abstract: The title of this study is “Morphosyntactic Study on English Derivational Suffixes Forming Adjectives with Reference to the Twilight”. This study discusses the combination of morphology and syntax called morphosyntax. Morphology is the study about word formation; meanwhile syntax is the study about sentence structure. This study mainly aims at finding out the derivational suffixes forming adjectives and the syntactic functions of the adjective found in the novel Twilight. The data of this study were taken from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…In analyzing the morphosyntactic of the English writing text, not only inflectional suffixes can be analyzed, but also derivational suffixes. The previous researcher, Antari & Sedeng (2018) conducted their rese arch on the title Morphosyntactic study of derivational suffixes forming adjective on the Twilight Novel. They found that there are certain derivational suffixes to transform word classes from nouns and verbs into adjectives.…”
Section: Previous Studies On Morphosyntactic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In analyzing the morphosyntactic of the English writing text, not only inflectional suffixes can be analyzed, but also derivational suffixes. The previous researcher, Antari & Sedeng (2018) conducted their rese arch on the title Morphosyntactic study of derivational suffixes forming adjective on the Twilight Novel. They found that there are certain derivational suffixes to transform word classes from nouns and verbs into adjectives.…”
Section: Previous Studies On Morphosyntactic Analysismentioning
confidence: 99%
“…Then, the suffixes (able, al, ing, ly, less, ful and ed) were added to noun stems to form adjective e.g., behavioural, proportional, personal, psychological, http://ijlllc.org/ essential, responsible, influencing, manufacturing, friendly, meaningless, mindful, and limited. Antari & Sedeng (2018) as the previous research conducted morphosyntactic analysis of derivational suffixes to change word class from noun and verb into adjective. They found that the suffixes -ful, -able, -ish, -ous, -al, -ic, less, -y, -ive, and -ly have been identified on the Twilight Novel.…”
Section: The Types Of Derivational Suffixesmentioning
confidence: 99%
“…Suffixes in derivational morphology do not play too much semantically on the basic form (Fernández Alcaina, 2021). Its main function is to change the basic form of word class (Mahendra & Indrawati, 2017).…”
Section: Derivational Suffixmentioning
confidence: 99%
“…There are five previous studies used as references in this study. The first prior study is an article done by Antari (2018) entitled "Morphosyntactic Study on English Derivational Suffixes Forming Adjectives with Reference to The Twilight." The aims of this study are to find out the derivational suffixes forming adjectives and its syntactic functions.…”
Section: Introductionmentioning
confidence: 99%